2022
DOI: 10.3389/fonc.2022.976224
|View full text |Cite
|
Sign up to set email alerts
|

Patients with melanoma treated with immune checkpoint inhibitors who had non-thyroid endocrine and skin immune-related adverse events have better prognosis: A systematic review and meta-analysis

Abstract: BackgroundSeveral studies have reported an association between the occurrence of immune-related adverse events (irAEs) and prognosis in patients with melanoma treated with immune checkpoint inhibitors (ICIs), but the results remain controversial. We conducted a systematic review and meta-analysis to investigate the association between irAEs and survival in patients with melanoma treated with ICIs.MethodsWe searched the PubMed, Web of Science, and China National Knowledge Infrastructure databases through May 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…In this study, 33.3% and 31.3% of patients were with dermatologic toxicities in the training cohort and validation cohort, respectively. Previous studies showed that dermatologic toxicities may be associated with positive antitumor response [50]. In this study, we found although dermatologic toxicities is not an independent prognostic factor for patients with advanced GC and EC treated with PD-1 inhibitor-based combination therapy, it is signi cantly correlated with their OS (P < 0.001).…”
Section: Discussionmentioning
confidence: 50%
“…In this study, 33.3% and 31.3% of patients were with dermatologic toxicities in the training cohort and validation cohort, respectively. Previous studies showed that dermatologic toxicities may be associated with positive antitumor response [50]. In this study, we found although dermatologic toxicities is not an independent prognostic factor for patients with advanced GC and EC treated with PD-1 inhibitor-based combination therapy, it is signi cantly correlated with their OS (P < 0.001).…”
Section: Discussionmentioning
confidence: 50%
“…Hence, the emergence of cirAEs can serve as a prognostic factor for patients with cancer undergoing ICI treatment. 2, [35][36][37][38] Additionally, to minimize potential bias associated with the varying durations of ICI exposure, we performed a landmark analysis for both PFS and OS among patients with a minimum exposure period of 6 weeks. The findings supported the hypothesis that the presence of cirAEs is associated with long-term therapeutic advantages (PFS and OS) among patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous meta-analyses that reported an association between cirAE prevalence and improved PFS and OS. Hence, the emergence of cirAEs can serve as a prognostic factor for patients with cancer undergoing ICI treatment . Additionally, to minimize potential bias associated with the varying durations of ICI exposure, we performed a landmark analysis for both PFS and OS among patients with a minimum exposure period of 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy and improved the treatment of patients with melanoma [ 1 ]. The most important immune checkpoint targets are cytotoxic T-lymphocyte antigen 4 (CTLA-4) and programmed cell death 1 (PD-1) or its ligand, programmed cell death ligand 1 (PD-L1).…”
Section: Introductionmentioning
confidence: 99%
“…Most irAEs appear within the first weeks to 3 months after initiation of ICIs [ 5 , 6 ], and female sex and younger age seem to be associated with higher rates of irAEs [ 7 , 8 ]. Previous studies have shown that irAEs predict improved tumor response and overall survival in metastatic cancer patients treated with ICIs [ 1 , 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%